The CRISP(Y) Future of Pediatric Soft Tissue Sarcomas - Pomella, Silvia; Rota, Rossella (Frontiers in Chemistry, 2020)
The RNA-guided clustered regularly interspaced palindromic repeats (CRISPR)/associated nuclease 9 (Cas9)-based genome editing technology has increasingly become a recognized method for translational research. In oncology, the ease and versatility of CRISPR/Cas9 has made it possible to obtain many results in the identification of new target genes and in unravel mechanisms of resistance to therapy. The majority of the studies have been made on adult tumors so far. In this mini review we present an overview on the major aspects of CRISPR/Cas9 technology with a focus on a group of rare pediatric malignancies, soft tissue sarcomas, on which this approach is having promising results.